2021
DOI: 10.1002/pcr2.10201
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar self‐nucleation behavior of a polybutene‐1/ethylene random copolymer

Abstract: The self‐nucleation behavior of a polybutene‐1/ethylene random copolymer, P(B1‐ran‐E), which undergoes a complex crystal‐crystal transition behavior, has been studied in detail. Similar to PE random copolymers, this material shows a strong melt memory effect even above equilibrium melting point of PB‐1 homopolymer. Different polymorphic forms can be obtained when P(B1‐ran‐E) is cooled from different self‐nucleation domains. The trigonal form I′ could only be nucleated in the presence of remaining form I crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It has been reported that lots of factors would affect the phase transition kinetics, such as the blending with other polymers, 25–28 copolymerization, 29–34 molecular weight, 35–37 temperature, 13,38,39 pressure, 40,41 extension, 11,12,42,43 nanofillers, 44–46 crystallization conditions, 47–52 and so on. Among all these factors, adding nanofillers and changing the crystallization conditions of form II are of significant value which can be used in the practical processing process to promote the phase transition process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that lots of factors would affect the phase transition kinetics, such as the blending with other polymers, 25–28 copolymerization, 29–34 molecular weight, 35–37 temperature, 13,38,39 pressure, 40,41 extension, 11,12,42,43 nanofillers, 44–46 crystallization conditions, 47–52 and so on. Among all these factors, adding nanofillers and changing the crystallization conditions of form II are of significant value which can be used in the practical processing process to promote the phase transition process.…”
Section: Introductionmentioning
confidence: 99%